Anti-apoptotic genes Bcl-2 and Bcl-xL overexpression can block iridovirus serine/threonine kinase-induced Bax/mitochondria-mediated cell death in GF-1 cells. Issue 61 (February 2017) - Reshi, Latif; Wang, Hua-Ven; Hui, Cho-Fat; Su, Yu-Chin; Hong, Jiann-Ruey
Abstract: Although serine/threonine (ST) kinase is known to induce host cell death in GF-1 cells, it remains unclear how ST kinase induces mitochondrial function loss. In the present study, we addressed the issue of mitochondrial function loss by determining whether the Bcl-2 family members Bcl-2 and Bcl-xL can prevent ST kinase-induced cell death activity via interacting with the pro-apoptotic gene Bax. Grouper fin cells (GF-1) carrying EGFP-Bal-xL and EGFP-Bcl-2 fused genes were selected, established in cell culture, and used to examine the involvement of Bcl-2 and Bcl-xL overexpression in protection of GF-1 cells from the effects of the giant sea perch iridovirus (GSIV) ST kinase gene. Using the TUNEL assay, we found that EGFP-Bcl-2 and EGFP-Bcl-xL reduced GSIV ST kinase-induced apoptosis to 20% all at 24 h and 48 h post-transfection (pt). Also, Bcl-2 and Bcl-xL substantially reduced the percentage of cells with GSIV ST kinase-induced loss of mitochondrial membrane potential (Δψps) at 24 and 48 hpt, respectively, and this reduction correlated with a 30% and 50% enhancement of host cell viability at 24 and 48 hpt as compared with vector control. Moreover, analysis of the effect of Bcl-2 and Bcl-xL interaction with Bax targeted to mitochondria during ST kinase expression at 48 hpt found that Bcl-2 and Bcl-xL also interacted with Bax to block cytochrome c release. Finally, Bcl-2 and Bcl-xL overexpression caused blockage of ST kinase function at 48 hpt, which was correlated with preventing caspase-9 and -3 cleavage and activation, thereby blocking downstream death signaling events. Taken together, our results suggest that the ST kinase-induced Bax/mitochondria-mediated cell death pathway can be blocked by the interaction of Bcl-2 and Bcl-xL with Bax to inhibit cytochrome c release during MMP loss. This rescue activity also correlated with inhibition of caspase-9 and -3 activation, thereby enhancing cell viability. Graphical abstract: Highlights: The novel death factor serine/threonine kinase can induce Bax-mediated cell death in fish cells. Overexpression of the Bcl-2 and Bcl-xL genes can repress the ST kinase-induced cell death and prevention of caspase-9 and -3 activations. The iridovirus ST kinase may provide a potential target for drugs that control viral escape.